Ava Ranga Uka A Toroke Hau, Chile. Die Arbeiten der Jahre 2017 und 2018 - Vogt, Burkhard (e-Forschungsberichte des DAI, 2018)
The site of Ava Ranga Uka a Toroke Hau in the heart of Easter Island has been excavated from 2008 to 2018. It was founded not later than the 13th century and was used probably until the 17th or early 18th century. The focus of investigation was the control and water management of a small creek, which embodied itself as a water and fertility sanctuary. The 2017 and 2018 field seasons allowed a much better understanding of the site highlighted by the discovery of a paved procession road, further water basins and channels, monumental terrace architecture, and the production of red pigment.